Acerola (Malpighia emarginata DC) and pineapple (Ananas comosus L. Merrill) as adjuncts in processing beer: characterization and acceptability - Luan Ãcaro Freitas Pinto (2015)
Beer is the most consumed alcoholic beverage in the world. Its consumption is associated with festivities and celebrations, being recognized by its customers as a beverage with high caloric value. However, this beverage contains a variety of bioactive compounds, vitamins and minerals that promote benefits when its intake is made moderate manner. The market is every day looking for different and even unique products, thus arises the field of craft beers. The objective of this study was to develop a craft beer with acerola and pineapple and study their physicochemical and sensory characteristics, as it brings a new alternative in this niche market, besides the association with increased its functional characteristics. We used the rotational central composite design (CCRD) for the development of treatments where the variation of the percentage of addition of the acerola fruit juice and pineapple varied at levels of 5 to 25% of the total volume of beer. The CCRD included eleven trials: four factorial points, four axial and three repetitions at the central point. The results of the CCRD were analyzed using the Response Surface Methodology (RSM), with the response variable physico-quÃmcos and sensory parameters. For statistical analysis was applied to analysis of variance, Tukey test and regression analysis. Processing took place in laboratory scale. The pulps were characterized by physical-chemical analysis, and then made by the addition of juice during the process of maturation that occurred simultaneously with primming process amber glass bottles of 355 ml. The results of the sugar content, total acids and pH of fruit pulps showed satisfactory being considered suitable for the maturation process. The results of physicochemical tests showed similar results in all treatments, and the factor adding fruit juice was directly proportional to parameters such as acidity and pH, and inversely proportional to parameters such as alcohol, real extract, apparent extract and extract primitive. Microbiological testing resulted in a minimum count of coliforms, thermotolerant and molds and yeasts, adapting to the standards set by law for beer, showing the process control efficiency, ensuring product quality. The means of the sensory attributes of all samples showed up outside the stopband, especially for samples 5 and 8, which have higher pineapple juice content. The results of the response surface showed that addition of up to 16% of both pulps pineapple or additions of high concentrations (up to 28%) in groups with low concentrations of acerola (up to 6%) show a maximization of sensory attributes. It was concluded that the use of pineapple pulp and acerola as adjuncts in the beer processing proved to be a viable alternative due to satisfactory results in sensory evaluation, and physical and chemical characteristics that proved a craft beer with acidy/fruity characteristics.